2016
DOI: 10.1155/2016/1679734
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Briquetting Process of Torrefied Rubber Seed Kernel and Palm Oil Shell

Abstract: Torrefaction process of biomass material is essential in converting them into biofuel with improved calorific value and physical strength. However, the production of torrefied biomass is loose, powdery, and nonuniform. One method of upgrading this material to improve their handling and combustion properties is by densification into briquettes of higher density than the original bulk density of the material. The effects of critical parameters of briquetting process that includes the type of biomass material use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Sengar et al [183] reported that cashew shell and grass briquettes took 0.68 and 0.63 years, respectively, as the project's payback period. However, the same project took 2.5 year for rice husk briquettes, which is slightly above the two-year period reported by Hamid et al [74] for the production of rubber seed kernel (RSK) and palm oil shell (POS) briquettes. In other studies, the payback period for durian peel and rice straw briquettes was 1.3 years [187] while peat briquettes production was between five and six years [184].…”
Section: Past Studies On Economic Analysis In Briefmentioning
confidence: 81%
“…Sengar et al [183] reported that cashew shell and grass briquettes took 0.68 and 0.63 years, respectively, as the project's payback period. However, the same project took 2.5 year for rice husk briquettes, which is slightly above the two-year period reported by Hamid et al [74] for the production of rubber seed kernel (RSK) and palm oil shell (POS) briquettes. In other studies, the payback period for durian peel and rice straw briquettes was 1.3 years [187] while peat briquettes production was between five and six years [184].…”
Section: Past Studies On Economic Analysis In Briefmentioning
confidence: 81%
“…Based on the observations, it was found that the microstructure of the briquettes is apparently finely textured for C-100/SPS-0, but has a coarse and rigid structure for C-90/SPS-10, C-80/SPS-20, C-70/SPS-30, and C-60/SPS-40 briquettes. This is due to the presence of SPS as the binder inside the composites, which can be observed from the increased amount of SPS, as shown in Figure 4 [ 19 , 34 ]. This microstructure proves that good bonding of the fine particles and decreased porosity were obtained for the briquettes with SPS loading compared to the neat ones.…”
Section: Resultsmentioning
confidence: 99%
“…There are however strong concerns about the amount of ash it may generate during combustion, as ash content in biomass above 4% may cause slagging [34]. Briquettes have been produced from some oil palm biomasses like the palm press fibers (PPF), palm kernel shell (PKS), mesocarp fiber (MF) and empty fruit bunch (EFB) [35][36][37][38][39][40]. Yet, very little or no attention has been given to OPT, as no studies can be traced to briquette made solely from OPT or mixed with another residue until now.…”
Section: Introductionmentioning
confidence: 99%